2007
DOI: 10.1137/060659107
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete LU Preconditioning with the Multilevel Fast Multipole Algorithm for Electromagnetic Scattering

Abstract: Iterative solution of large-scale scattering problems in computational electromagnetics with the multilevel fast multipole algorithm (MLFMA) requires strong preconditioners, especially for the electric-field integral equation (EFIE) formulation. Incomplete LU (ILU) preconditioners are widely used and available in several solver packages. However, they lack robustness due to potential instability problems. In this study, we consider various ILU-class preconditioners and investigate the parameters that render th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
93
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 28 publications
(42 reference statements)
1
93
0
Order By: Relevance
“…Recently, we showed that an ILU preconditioner without a threshold provides an inexpensive and good approximation to the solution of the near-field matrix for CFIE, hence it reduces the iteration counts and solution times substantially [18]. For ill-conditioned EFIE matrices, however, ILUT (i.e., threshold-based ILU) with pivoting [19] is required to prevent the potential instability.…”
Section: Preconditioners Built From Near-field Matricesmentioning
confidence: 99%
“…Recently, we showed that an ILU preconditioner without a threshold provides an inexpensive and good approximation to the solution of the near-field matrix for CFIE, hence it reduces the iteration counts and solution times substantially [18]. For ill-conditioned EFIE matrices, however, ILUT (i.e., threshold-based ILU) with pivoting [19] is required to prevent the potential instability.…”
Section: Preconditioners Built From Near-field Matricesmentioning
confidence: 99%
“…To obtain a convergence in a reasonable number of iterations, we employ enhanced preconditioning techniques that are also convenient for MLFMA implementations. For example, we consider preconditioners based on incomplete LU (ILU) factorization [10] or sparse approximate inverse (SAI) of the near-field matrix [1]. Although these preconditioners provide efficient solutions for ordinary frequencies, formulations at resonance frequencies lead to very ill-conditioned matrix equations, which need further information than that provided by the near-field matrix for a convergence.…”
Section: Nested Preconditionersmentioning
confidence: 99%
“…In this paper, we propose a novel technique denoted as the hybrid CFIE-IEFIE to accelerate the convergence rate, which replaces the EFIE part in the hybrid CFIE-EFIE techniques with the improved electric field integral equation (IEFIE) [17]. To further accelerate the solution, the incomplete LU preconditioning technique in [18,19] is proposed to solve the hybrid CFIE-IEFIE.…”
Section: Introductionmentioning
confidence: 99%
“…There are two popular drop strategies for ILU factorization: the level based drop strategy and the threshold based drop strategy, the former is denoted ILU(p), where p ≥ 0 is an integer denoted as the level of fill-in, and the latter is ILUT. The ILU-class preconditioners have been tested for electromagnetic problems in [19]. It can be found that ILU(0) preconditioner produces highly unstable and hence useless factorizations for the EFIE as the number of unknowns increases.…”
Section: Introductionmentioning
confidence: 99%